Immagine dogmatica e immagine teatrale del pensiero - Remiddi, Sofia (Scenari, 2024)
The present contribution aims to emphasize the subversive and positive centrality of the image in the initial deleuzian thought and to emphasize its aesthetic attributes, particularly regarding the theatre and the concept of dramatization. To achieve this, the work begins by examining the implications of the dogmatic representation of thought. The image is surrounded by negativity, which leads Deleuze to search for a thought that is free of it, but it fails to explain the proposal for a new image of thought. This oscillation will be resolved in the last part of the article by focusing on the importance of that image without similarity which is the simulacrum whose aesthetic value is central both in relation to transcendental empiricism, and in leading to an exercise of thought explained by Deleuze through the art of theatre.